Gender-associated genes in filarial nematodes are important for reproduction and potential intervention targets. - Ben-Wen Li; Amy C Rush; Dao-Jun Jiang; Makedonka Mitreva; Sahar Abubucker; Gary J Weil (Public Library of Science (PLoS), 2011)
BACKGROUND: A better understanding of reproductive processes in parasitic nematodes may lead to development of new anthelmintics and control strategies for combating disabling and disfiguring neglected tropical diseases such as lymphatic filariasis and onchocerciasis. Transcriptomatic analysis has provided important new insights into mechanisms of reproduction and development in other invertebrates. We have performed the first genome-wide analysis of gender-associated (GA) gene expression in a filarial nematode to improve understanding of key reproductive processes in these parasites. METHODOLOGY/PRINCIPAL FINDINGS: The Version 2 Filarial Microarray with 18,104 elements representing ∼85% of the filarial genome was used to identify GA gene transcripts in adult Brugia malayi worms. Approximately 19% of 14,293 genes were identified as GA genes. Many GA genes have potential Caenorhabditis elegans homologues annotated as germline-, oogenesis-, spermatogenesis-, and early embryogenesis- enriched. The potential C. elegans homologues of the filarial GA genes have a higher frequency of severe RNAi phenotypes (such as lethal and sterility) than other C. elegans genes. Molecular functions and biological processes associated with GA genes were gender-segregated. Peptidase, ligase, transferase, regulator activity for kinase and transcription, and rRNA and lipid binding were associated with female GA genes. In contrast, catalytic activity from kinase, ATP, and carbohydrate binding were associated with male GA genes. Cell cycle, transcription, translation, and biological regulation were increased in females, whereas metabolic processes of phosphate and carbohydrate metabolism, energy generation, and cell communication were increased in males. Significantly enriched pathways in females were associated with cell growth and protein synthesis, whereas metabolic pathways such as pentose phosphate and energy production pathways were enriched in males. There were also striking gender differences in environmental information processing and cell communication pathways. Many proteins encoded by GA genes are secreted by Brugia malayi, and these encode immunomodulatory molecules such as antioxidants and host cytokine mimics. Expression of many GA genes has been recently reported to be suppressed by tetracycline, which blocks reproduction in female Brugia malayi. Our localization of GA transcripts in filarial reproductive organs supports the hypothesis that these genes encode proteins involved in reproduction. CONCLUSIONS/SIGNIFICANCE: Genome-wide expression profiling coupled with a robust bioinformatics analysis has greatly expanded our understanding of the molecular biology of reproduction in filarial nematodes. This study has highlighted key molecules and pathways associated with reproductive and other biological processes and identified numerous potential candidates for rational drug design to target reproductive processes.